(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
Information Technology have to be an enabler of every activity. With the information technology, the effectiveness and efficiency of work shoultd be increase. The obstacles faced, with the existence of information technology, can be an alternative solution. SDN Hurip Jaya 03 Babelan is a school located on the north coast of Bekasi Regency. This school has a challenge where cable internet access from Provider has not yet entered so that educators and education staff, students use independent resources for internet access. Administrative and learning activities already use computers but have not utilized cloud applications such as google forms, google classroom, and shorter url applications for learning e-learning. The educators and education staff are also still working with computers in typing so that their work is less effective. The solution we provide is to share knowledge, knowledge, experience and resources in providing solutions to existing problems. The activities that have been carried out are providing wifi modem and usb wifi resources for internet access, training in fast typing the 10 finger method, using google forms and google classroom for administration and learning, as well as the bit.ly application for naming links to make reading easier. We hope that if the material presented can be trained and applied seriously, it will certainly be useful in supporting administrative and learning activities.